Investigation of Cardio Exercise's Effects on Body Perception and Life Satisfaction in Relation with Some Parameters - Okan Volkan Karatan; Gulsum Baştuğ; Kemal Göral; Sümmani Ekici (Türk Spor ve Egzersiz Dergisi)
The aim of this study was to investigate the effect of cardio exercise together with some parameters on body perception and life satisfaction. 48 sedentary individuals between 20-45 years old were voluntarily participated in the study. 14-week cardio Exercise was applied to Experimental group and body weight, height, body fat percentage, body mass index, metabolism rate measurements of participants in experimental-control group were taken as pretest-posttest. “Body Areas Satisfaction” sub-dimension of “The Multidimensional Body-Self Relations Questionnaire (MBSRQ)” scale was used to determine the body perception levels of participants in the research whereas "Life Satisfaction with Life Scale” was used to determine their life satisfaction levels. As a result; a significant difference was found between pretest and posttest values of body weight, body fat percentage, body mass index, metabolism rate, life satisfaction and body perception of males and females doing cardio exercises (experimental group). Depending on cardio exercise program, a positive development was determined in body weight, body mass index, body fat percentage, metabolism rate, life satisfaction and body perception properties of females and males in experimental group. It was considered that cardio exercise program positively changed life satisfaction and body perception level with physiological parameters.